Using vosviewer to analyze articles, indexing in pubmed database, about emerging infections - Shkola, Ihor; Andriichuk, Mariia; Petruniok, Alina (The Ukrainian Scientific Medical Youth Journal, 2022)
emerging infections are becoming increasingly important in today's globalized world, are spreading rapidly and have extraordinary socio-economic consequences, they are being studied by scientists from many countries. The study of emerging diseases takes place in many areas and aspects, in various fields of knowledge, including and using bibliometrics. VOS viewer, as a multifunctional tool for analyzing bibliometric networks, provides an opportunity to visualize the relationships between keywords and authors. The aim of the work. Using the VOS viewer tools for bibliographic analysis of articles from the PubMed database to identify trends in scientific publications on emerging infections and, on this basis, identify key factors in the emergence of modern emerging infections. Research methods. To conduct bibliometric analysis, the VOS viewer toolkit was used, which made it possible to build maps for visualizing the interdependence between various aspects, which are reflected in publications indexed in the PubMed database at the request “Emerging infectious”. Results and discussion. Information on scientific publications from the PubMed database on the topic "Emerging infectious" for the period 1952 - 2021 in the amount of 66,910 was used. VOS viewer software gave the authors the opportunity to identify 5 clusters for 952 keywords (including the cluster "Factors influencing the spread of emergent diseases") and to reveal the causes and mechanisms of emergent infections. Conclusions. Bibliometric analysis has revealed trends in the active study of emergent diseases as particularly dangerous infections in many countries, but in Ukraine there is no scientific interest in this problem, although many preconditions for the spread of these diseases, and biosafety of Ukrainian society needs urgent solution.